Case Report: Intellectual disability and borderline intellectual functioning in two sisters with a 12p11.22 loss - Choi, Haemi; Kim, Jeong-A.; Cho, Kyung-Ok; Kim, Hyun Jung; Park, Min-Hyeon (Frontiers in Genetics, 2024)
Multiple genome sequencing studies have identified genetic abnormalities as major causes of severe intellectual disability (ID). However, many children affected by mild ID and borderline intellectual functioning (BIF) lack a genetic diagnosis because known causative ID genetic mutations have not been identified or the role of genetic variants in mild cases is less understood. Genetic variant testing in mild cases is necessary to provide information on prognosis and risk of occurrence. In this study, we report two sibling patients who were 5 years 9 months old and 3 years 3 months old and presented to the hospital due to developmental delay. Clinical assessment and chromosomal microarray analysis were performed. The patients were diagnosed with mild intellectual disability (ID) and borderline intellectual functioning (BIF). Genetic analysis identified a loss of 12p11.22, including the OVCH1-AS1, OVCH1, and TMTC1 genes, which was the only variant that occurred in both sisters. Identical variants were found in their father with probable BIF. Neither patient presented any brain structural abnormalities or dysmorphism, and no exogenous factors or parenting problems were reported. Thus, loss of 12p11.22 may be associated with our patients' cognitive impairment. The OVCH1, OVCH1-AS1 and TMTC1 variants identified in this study are the most likely diseasecausing genes in the sisters. Our findings may expand as yet limited knowledge on mild ID and BIF causative variants, which would further support the diagnosis even if the severity is mild.